2020
DOI: 10.3389/fmicb.2020.572706
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Season and Soil Properties on Fungal Communities of Neighboring Climax Forests (Carpinus cordata and Fraxinus rhynchophylla)

Abstract: Trees in forest ecosystems constantly interact with the soil fungal community, and this interaction plays a key role in nutrient cycling. The diversity of soil fungal communities is affected by both environmental factors and host tree species. We investigated the influence of both of these factors by examining the total fungal communities in the rhizospheric soil of climax tree species that have similar ecological roles (Carpinus cordata, an ectomycorrhizal [ECM] tree, and Fraxinus rhynchophylla, an arbuscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…The distributions of fungi (the relative abundance of dominant fungal genera >78%) and bacteria (the relative abundance of dominant bacterial genera >21%) in three collection sites were not uniform, which revealed that a few dominant species are responsible for the higher relative abundance ( Tables S1 and S3 ). In the Carpinus cordata forest, Inocybe , Sebacina , Tomentella and Russula account for 29% of the relative abundance [ 69 ]. The community compositions of EMF showed the same pattern that a few dominant genera account for the majority of the relative abundance in different forests [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distributions of fungi (the relative abundance of dominant fungal genera >78%) and bacteria (the relative abundance of dominant bacterial genera >21%) in three collection sites were not uniform, which revealed that a few dominant species are responsible for the higher relative abundance ( Tables S1 and S3 ). In the Carpinus cordata forest, Inocybe , Sebacina , Tomentella and Russula account for 29% of the relative abundance [ 69 ]. The community compositions of EMF showed the same pattern that a few dominant genera account for the majority of the relative abundance in different forests [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Habitat and geographical distribution: Saprobe on submerged wood, known only from Asia, China [29]. According to GlobalFungi, the identical sequences were found in 12 samples of rhizosphere soil (92%) or soil (8%) collected in forest (92%) or grassland (8%) habitats in Asia in North East China and South Korea [155,156]. The locations have a cold and humid climate (MAT avg.…”
Section: Taxonomymentioning
confidence: 99%
“…Especially, the soil of the Zhongning region is poor with lower soil physicochemical indicators, but it has a higher abundance of AMF species. Many studies suggest that soil pH significantly affects the AMF communities ( 33 , 35 , 63 66 ). For example, alkaline soils in forest ecosystems positively affect the AMF communities ( 67 ), while acidic soils negatively affect the AMF spore density and evenness ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the host plants can have a controlling effect on AMF colonization ( 30 ). So far, most studies have only focused on the sampling sites at different locations to examine the correlation between soil physicochemical factors and AMF communities ( 31 33 ). Apart from soil physicochemical properties, soil enzyme activity, soil temperature, soil moisture, and the relative contributions of relevant environmental factors such as altitude, relative air humidity, soil pH, and available phosphorus (P), kalium (K), and magnesium (Mg) can influence the AMF spore production and root colonization ( 32 , 34 36 ).…”
Section: Introductionmentioning
confidence: 99%